2018
DOI: 10.1634/theoncologist.2017-0573
|View full text |Cite
|
Sign up to set email alerts
|

Trifluridine/Tipiracil (TAS-102) in Refractory Metastatic Colorectal Cancer: A Multicenter Register in the Frame of the Italian Compassionate Use Program

Abstract: Improving the cost-efficacy ratio of TAS-102 in metastatic colorectal cancer is needed to spare useless toxicities in a definitely palliative setting. Eastern Cooperative Oncology Group performance status, lactate dehydrogenase levels, and time from the diagnosis of metastatic disease may help to identify patients more likely to achieve benefit. Properly designed prognostic tools (i.e., the "ColonLife" nomogram) may enable excluding from further treatments patients with very limited life expectancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
35
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 27 publications
17
35
0
2
Order By: Relevance
“…One hundred twenty-one patients received both regorafenib and trifluridine/tipiracil, and no differences were observed in the first or second PFS and OS between the 2 sequences. 20 Other experiences of expanded use in countries such as Spain or Great Britain also obtained comparable results to those of the RECOURSE study. 21,22 In terms of predictive factors of response, no differences were observed regarding age or RAS status in the RECOURSE study.…”
Section: Trifluridine/tipiracilsupporting
confidence: 59%
“…One hundred twenty-one patients received both regorafenib and trifluridine/tipiracil, and no differences were observed in the first or second PFS and OS between the 2 sequences. 20 Other experiences of expanded use in countries such as Spain or Great Britain also obtained comparable results to those of the RECOURSE study. 21,22 In terms of predictive factors of response, no differences were observed regarding age or RAS status in the RECOURSE study.…”
Section: Trifluridine/tipiracilsupporting
confidence: 59%
“…Subsequent post-hoc analysis of RECOURSE trial data has demonstrated the clinical efficacy and tolerability of trifluridine/tipiracil in various subgroups [11] and clinically meaningful improvements in quality-adjusted survival [12]. There is further evidence supporting the clinical effectiveness and tolerability of trifluridine/tipiracil in various geographies [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 97%
“… 4 Interestingly, a number of groups have recently reported that the onset of CIN is an indication of better treatment outcomes in mCRC patients treated with FTD/TPI, 5 7 with the development of higher-grade CIN (grade ≥3) at any time of FTD/TPI treatment being associated with longer PFS and OS. 8 …”
Section: Introductionmentioning
confidence: 99%